'The prodigal child': a legal inquiry into the mechanisms for the rehabilitation and reintegration of juvenile detainees: lessons from Mauritius - Bissessur, Pramod (University of Pretoria, 2010)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2009.